Entrepreneurship /Robert D Hisrich, Michael P Peters, Dean A Shepherd. - Hisrich, Robert D.
Aims to instruct students on the process of formulating, planning, and implementing a new venture. This book reveals descriptions of how to embark on a new venture in a logical manner. It includes comprehensive cases at the end of the text that have been hand-picked by the authors to go hand-in-hand with chapter concepts.